Isolation of Homogenous Population of Human Amniotic Epithelial Stems Cells - Qurat ul ain khan; Bushra wasim; Kanwal Haneef; Talat Mirza; Shumaila Usman (ziauddin University, 2024)
Background: Regenerative medicine is a collaborative field that applies combined concepts of tissue engineering and cell biology to promote regeneration. Tissue regeneration initiate the emergence of remedies that can replace and revive tissues and loss of organs through illness and injury and reduce dependency on organ transplantation. The objective was to isolate a homogenous population of human amniotic epithelial stem cells (hAECs) and to determine their phenotype under a live-cell imaging microscope at 1st, 3rd and 8th-day intervals. Methods: This was an experimental in-vitro study conducted on human placenta (amniotic epithelial stem cells) at Ziauddin Hospital and University. The 22 human placenta were collected from patients with age 20-30 years having healthy full-term pregnancies, with a preference for elective cesarean sections. In vitro isolation of human amniotic epithelial stem cells was used after manual removal of the amniotic membrane from the chorionic membrane of human term placenta via single-step enzymatic digestion. The morphology of the attached cells was analyzed at different magnifications i.e., 10X, 20X and 40X. Results: The isolated human amniotic epithelial stem cells on day 3 started forming colonies and attained a characteristic cuboid epithelial shape and exhibited a confluent single layer on day 8. Morphologically resembled cobblestones with a characteristic of fully vacuolated cytoplasm were found uncontaminated with spindle-shaped human amniotic mesenchymal stem cells (MSCs). Conclusion: The isolated population of hAESCs were highly proliferative and not contaminated with MSCs. Therefore, this optimized protocol may be used for the isolation and the biobanking of hAESCs for future cellular transplantation. Keywords: Human Amniotic Epithelial Stem Cells (hAESCs); Regenerative Medicine; Perinatal Stem Cells; Placental Membrane; Amniotic Membrane.